2021
DOI: 10.33225/pec/21.79.47
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Experiences of Women Principals in Primary Schools in Limpopo Province, South Africa Through Social Justice Theory

Abstract: School leadership research has provided extensive empirical evidence which shows that women as school leaders face challenges on many fronts. The objective of this study was to provide insight regarding the challenges that female primary school principals face, in the Waterberg Education District, Limpopo Province, South Africa. These challenges were in respect of the perception of staff members towards women as school principals. This study was qualitative and interpretive in nature. The theory of social just… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…Studies on women in leadership suggest that female leaders continue to face barriers in leadership contexts in schools and higher education (Lowe et al, 2011;Hacifazlioglu, 2010;Nyoni et al, 2017;McCullough, 2020;Khumalo, 2021). Studies representing women samples through a wide range of geographical regions from Australia, North America, Africa, Asia and the Middle East, indicate that they endured challenges regardless of their belonging to a certain culture or geographic location.…”
Section: Women In Leadershipmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies on women in leadership suggest that female leaders continue to face barriers in leadership contexts in schools and higher education (Lowe et al, 2011;Hacifazlioglu, 2010;Nyoni et al, 2017;McCullough, 2020;Khumalo, 2021). Studies representing women samples through a wide range of geographical regions from Australia, North America, Africa, Asia and the Middle East, indicate that they endured challenges regardless of their belonging to a certain culture or geographic location.…”
Section: Women In Leadershipmentioning
confidence: 99%
“…In countries like Saudi and Qatar, women leaders face challenges in breaking the boundaries of traditional bureaucracies (Vogel & Alhudeithi, 2018) which are mostly navigated by men. Placement in leadership positions based on qualifications is not evident in African countries (Barmao, 2013;Reilly, 2015;Nyoni et al, 2017;Iyekolo, Okafor & Abdulaziz, 2020;Khumalo, 2021) where gender disparity continues to "hinder women from aspiring to leadership positions" (Barmao, 2013: p. 51) since leadership is still regarded as a "masculine domain" (Nyoni et al, 2017). Studies on women in Pakistan and Afghanistan assert that the proportion of educated women is very low (Malik, 2011;Reilly 2015).…”
Section: Barriers Know No Bordersmentioning
confidence: 99%
See 2 more Smart Citations
“…such harassment exists on our streets, in our workplaces and in virtually in every sphere where men and women interact." Khumalo (2021) in her study of female principals in South Africa concluded that sexual harassment is entrenched in schools, given the prevalence and frequency at which female principals are harassed by superiors and subordinates alike. Komaromy, Bindman, Haber and Sande (1993) in their research on the prevalence of sexual harassment in medical school indicated that "a large percentage of medical students (36 to 52) reported experiencing some form of sexual harassment during medical school" and that "such harassment creates a high level of stress."…”
Section: What Is Sexual Harassment?mentioning
confidence: 99%